ASSOCIATION OF SERUM AMH WITH LABORATORY AND PHENOTYPE IN WOMEN WITH PCOS: A RETROSPECTIVE STUDY - Özlem Karabay Akgül; Nurşen Kurtoğlu Aksoy (Sabiad)
Objective: The aim of this study was to compare the endocrine and phenotypic characteristics of PCOS women with serum AMH levels of 4‑10 ng/mL and >10 ng/mL, and to investigate the importance of high AMH levels in the diagnosis of PCOS. Materials and Methods: In this retrospective cohort study, the laboratory and demographic characteristics of women with serum AMH ≥4 ng/mL whose follow-up was initiated at the infertility outpatient clinic of a tertiary health care institution were investigated. Fasting levels of HOMA, LH, FSH, estradiol, androstenedione, total testosterone, prolactin, 17Oh progesterone, DHEAS and AMH were recorded from hospital records. Age, gravidity, BMI, infertility status, hirsutism, menstrual cycle and ultrasonographic ovarian morphology were recorded. Patients were divided into two groups, as those with serum AMH values of 4‑10 ng/mL and those with serum AMH values of >10 ng/mL. Women with AMH >10 ng/mL were defined as the “high AMH group” and those with AMH >14 ng/mL were defined as the “very high AMH group.” Women on hormone-containing drugs, metformin, and/or chronic medication, as well as women with endocrine organ tumors and/or who have had ovarian surgery were excluded. Results: The patients were between 21 and 38 years of age. Fifty-four women with AMH values of 4‑10 ng/mL, 12 women with 10‑14 ng/mL and 16 women with >14 ng/mL were included in the study. Forty-four patients were primary infertile, and 28 patients had clinical hirsutism. Women with high AMH values had more primary infertility and hirsutism. Thirty-four patients had menstrual irregularities, and there was no statistically significant difference between the two groups in terms of menstrual irregularities. Among laboratory values, total testosterone, androstenedione, and the LH/FSH ratio were significantly associated with high AMH. Primary infertility and hirsutism were more common in women with high AMH. PCOM was seen in all the women with AMH >10 ng/mL. There was no difference between the two groups in terms of HOMA and BMI criteria. Other endocrine values were not associated with AMH levels. Conclusion: There is a positive correlation between androgens and AMH in women with high AMH values, with the possibility of high AMH being an additional marker for the diagnosis of PCOS. We believe that women with hirsutism and high amounts of androgens and especially women with PCOM may have high AMH, and infertility treatments should be organized by taking into account the related drug resistance.